Cecum perforation following intrauterine device insertion: a case report - Maryam FaridMojtahedi; Atefeh Khezri (Mashhad University of Medical Sciences, 2022)
Introduction: Intrauterine device (IUD) is an effective and reliable contraceptive method. It is one of the most frequently used methods in our country. Colon perforation is a rare but serious complication occurring sometimes years after insertion. In this report, a patient with cecum perforation following IUD insertion who presented with acute abdomen was reported. Case Presentation: The patient was a 30 year old female who admitted to the clinic of Arash Women's Comprehensive Hospital with complaints of hypogastric abdominal pain and spotting. She had a natural vaginal delivery 6 months ago and an IUD was inserted one week before referring. On abdominal examination, there was pain in the hypogastric region with deep palpation and there was positive cervical motion tenderness. Abdominal ultrasonography did not show IUD in uterine cavity. Abdominal X-ray was done and IUD was seen in abdominal cavity. Emergent Laparascopy was done. Two cecum perforations by an intrauterine device were diagnosed, and the intestinal damage was repaired with a laparatomic approach. Conclusion: IUD migration and uterine and colon perforation is a rare but serious complication that should be considered in differential diagnosis of each woman with IUD who has abdominal pain. Laparoscopic approach for intrauterine device removal is a simple and safe approach if further complications are not likely.